FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR CENGKEH INDONESIA TAHUN 2001-2015 - Rhezamayye, Veronica; Amir, Indra Tjahaja; abidin, Zainal (Berkala Ilmiah AGRIDEVINA, 2019)
Cloves origin Indonesia has been known since the 17th century. The presence of clove cigarette factory to make the production of national cloves absorbed in the domestic market so that the amount exported quite fluctuate. In addition to useful food and cooking spices, cloves in certain countries such as China and Japan are in demand for incense makers used in religious ceremonies. This study aims to identify the factors that influence and examine how much influence the amount of production, domestic consumption, domestic prices, export prices and exchange rates on clove export volume in 2001-2015. Data analyzed descriptively analytical with quantitative approach and using equation multiple linear regression. The results showed that production, domestic consumption, domestic prices, export prices and exchange rates had a 53.2% and significant effect on Indonesian clove exports from 2001-2015. Government policy support in empowerment of extension and farmer group organization is needed to increase clove production in Indonesia, so as to increase the export volume of cloves. DOI : https://doi.org/10.33005/adv.v8i2.1805